Exploring the dynamics of a single vesicle induced by Fe₃O₄ nanoparticles using micropipette manipulation - Nazia Ahmed; Tawfika Nasrin; Mohammad Abu Sayem Karal (PLoS ONE, 2025)
Magnetite nanoparticles (MNPs, Fe3O4) have gained substantial interest for different biomedical and biochemical applications. Therefore, it is important to understand the mechanism of interaction between MNPs and cell membranes. As a model for cells, giant unilamellar vesicles (GUVs) are used in various research studies, providing valuable insights into the behavior of lipid bilayers and their interactions with MNPs. To understand the mechanism of interaction between MNPs and membranes, the dynamics of a ‘single GUV’ are explored using the micropipette technique under physiological conditions. The GUVs exhibited deformation upon adsorption of anionic MNPs into the membrane, with the degree of deformation (e.g., compactness) increasing over time. The addition of MNPs through a micropipette into the vicinity of a ‘single GUV’ induced various shape changes; for example, a prolate shape transformed into two spheres connected by a neck. The fraction of the shape changes of GUVs increased with the concentration of MNPs. These results indicated that MNPs were absorbed onto the outer monolayer, inducing an area mismatch between the outer and inner monolayers of the membrane. The change in membrane area upon MNP binding in a ‘single GUV’ was investigated using the micropipette aspiration technique. Initially, the membrane area increased at a faster rate until reaching a saturation point, then decreased at a slower rate back to the original point, followed by a slight increase at a very slow rate. These changes suggest rapid stretching, slower compression, and finally slow stretching in the membranes of the GUV. Based on these results, we discuss the interaction mechanism of anionic MNPs with a single GUV.